Análise crítica de gênero do Enem de língua inglesa - Radünz, Amanda Petry (2020)
This master’s thesis focuses on the analysis of the genre English language (EL) reading test using Critical Genre Analysis’ (CGA) theoretical and methodological assumptions (MOTTA-ROTH, 2006; 2008a; 2008b). More specifically, the scope of the study is the Brazilian national high school exam (ENEM), an exam that is used to apply to universities and to participate in projects that facilitate the access to higher education, such as University for All (Prouni) and Student Financing Program (FIES). Considering its national importance, recent studies have analyzed the Mathematics (CAPELLA, 2018), the Biology, Physics and Chemistry (RODRIGUES, 2018; SILVA; SOUZA, 2018), and the Foreign Language (PINHEIRO; QUEVEDO-CAMARGO, 2017; AZEVEDO et al., 2018; OLIVEIRA, 2019) tests at ENEM. However, among the studies in the Linguistics field, there are no studies that analyze ENEM as a genre sample. Thus, the objective of this paper is to analyze the ENEM-EL as a genre sample using CGA theoretical and methodological assumptions. The paper’s specific objectives are: 1) to investigate the rhetorical organization of the genre ENEM-EL; 2) to identify the language strata (Phonology and Graphology; Lexicogrammar; Semantics and Pragmatics; Register; Genre; Discourse (MOTTA-ROTH, 2008a, p. 352)) explored by the items that compose the ENEM-EL; and 3) to delineate the language conception that underlies this test. The corpus of the study is composed of 40 EL items at ENEM editions applied between 2010 and 2017. The analysis procedures concerned the context and text analysis. The context analysis considered official documents that refer to ENEM, and the text analysis considered the reference texts, instructions and alternatives that compose the 40 items of the corpus, in order to identify the typical rhetorical organization of the genre, the language strata explored by the items, and the language conception that underlies this test. The results point that the items, organized on three rhetorical moves, provide, on the instructions, information concerning the reference texts’ context, which belong to the journalistic, literary, pedagogic, advertising and touristic spheres. Besides, the items demand, mainly, specific information about the reference text’s content, proposal and topic. This way, on ENEM-EL, the language strata directly mobilized are the Semantics and Pragmatics, Register and Genre strata, indicating a direction to the view of language as genre, adopted by the official documents that guide ENEM’s formulation.